2015
DOI: 10.1111/appy.12191
|View full text |Cite
|
Sign up to set email alerts
|

Screening for depression and anxiety among older Chinese immigrants living in Western countries: The use of the Geriatric Depression Scale (GDS) and the Geriatric Anxiety Inventory (GAI)

Abstract: Results of this review have practical implications for clinicians in their use of these tools with older Chinese immigrants in Western countries, such as the different GDS versions. It also suggests a number of directions for future research, such as the inclusion of clinical samples and consideration of the diversity within this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 41 publications
6
33
1
2
Order By: Relevance
“…The survey results showed that the prevalence of depressive features in the elderly was 47.4% (45.9% in male and 48.5% in women). These results are higher than those observed in India (39.1%), 19 in Hong Kong (30.0%), 20 amongst elderly Chinese immigrants in Western countries (20.0% – 30.0%), 21 and in South Korea (26.0%), 22 as well as being lower than that of elderly Chinese (59.8%) 16 reported in previous studies. The differences may be due to a difference in sampling design, assessment tools for depressive features or objects of study.…”
Section: Discussioncontrasting
confidence: 64%
“…The survey results showed that the prevalence of depressive features in the elderly was 47.4% (45.9% in male and 48.5% in women). These results are higher than those observed in India (39.1%), 19 in Hong Kong (30.0%), 20 amongst elderly Chinese immigrants in Western countries (20.0% – 30.0%), 21 and in South Korea (26.0%), 22 as well as being lower than that of elderly Chinese (59.8%) 16 reported in previous studies. The differences may be due to a difference in sampling design, assessment tools for depressive features or objects of study.…”
Section: Discussioncontrasting
confidence: 64%
“…Quality of life of the elderly with pain was compromised in the eight domains evaluated. These findings are corroborated by several studies showing that quality of life related to health is lower in patients with chronic pain, compared with healthy individuals 40 44 Some authors suggest that pain is the main cause of deteriorating quality of life. 45 …”
Section: Discussionsupporting
confidence: 56%
“…Scores above 5 are consistent with clinical depressive symptoms. The GDS has been successfully used for screening depressive symptoms [ 37 ]. See Table 1 for results.…”
Section: Methodsmentioning
confidence: 99%